Fluoride Release and Recharge from Different Materials Used as Fissure Sealants - Bayrak, Sule; Tunc, Emine Sen; Aksoy, Abdurrahman; Ertas, Ertan; Guvenc, Dilek; Ozer, Sezin (European Journal of Dentistry, 2010)
Objectives: Fluoride release/recharge properties of fissure sealants are important for their longterm inhibition of caries. This study was conducted to examine the relationship between fluoride release and recharge of pit-and-fissure sealants.Methods: Specimens were prepared from 5 different sealant materials: Fissurit F, a conventional resin; Fuji VII, a glass-ionomer cement (GIC); Fuji II LC, a resin-modified GIC; Ionosit, a polyacidmodified composite resin (PMRC); and Aelite Flo, a flowable composite resin. Specimens stored in a polyethylene test tube containing 5.0 ml ultrapure water. On day 21, specimens were exposed to 1.23% APF gel. Fluoride release was measured using a fluoride-specific ion electrode at 1-7, 14, 21, 22, 28, 35 and 42 days.Results: The glass-ionomer based sealants Fuji VII and Fuji II LC had significantly higher fluoride release than the other materials at all times tested (P<.05). Fluoride release of all materials tested increased following exposure to APF gel (P<.05).Conclusions: Within the limitations of this short-term study, glass ionomer-based sealants were shown to have higher initial fluoride release as well as higher fluoride recharge capacity than other sealants. (Eur J Dent 2010;4:245-250)
Keywords: Fissure sealant; Fluoride release; Fluoride recharge; Preventive dentistry; Topical fluoride